Increased risk of SARS-CoV-2 infection in staff working across different care homes: enhanced CoVID-19 outbreak investigations in London care Homes - Ladhani, Shamez N; Chow, J. Yimmy; Janarthanan, Roshni; Fok, Jonathan; Crawley-Boevey, Emma; Vusirikala, Amoolya; Fernandez, Elena; Perez, Marina Sanchez; Tang, Suzanne; Dun-Campbell, Kate; Wynne-Evans, Edward; Bell, Anita; et al. (The Journal of infection, 2020)
•21% of 255 staff working in 6 care homes with a COVID-19 outbreak were SARS-CoV-2 positive.•SARS-CoV-2 positivity was similar in staff with regular (18%), occasional (16%) or no (15%) resident contact.•SARS-CoV-2 positivity was 3-fold higher in staff working across different care homes.•Whole genome sequencing identified distinct clusters involving staff only. Care homes have been disproportionately affected by the COVID-19 pandemic and continue to suffer large outbreaks even when community infection rates are declining, thus representing important pockets of transmission. We assessed occupational risk factors for SARS-CoV-2 infection among staff in six care homes experiencing a COVID-19 outbreak during the peak of the pandemic in London, England. Care home staff were tested for SARS-COV-2 infection by RT-PCR and asked to report any symptoms, their contact with residents and if they worked in different care homes. Whole genome sequencing (WGS) was performed on RT-PCR positive samples. In total, 53 (21%) of 254 staff were SARS-CoV-2 positive but only 12/53 (23%) were symptomatic. Among staff working in a single care home, SARS-CoV-2 positivity was 15% (2/13), 16% (7/45) and 18% (30/169) in those reporting no, occasional and regular contact with residents. In contrast, staff working across different care homes (14/27, 52%) had a 3.0-fold (95% CI, 1.9–4.8; P<0.001) higher risk of SARS-CoV-2 positivity than staff working in single care homes (39/227, 17%). WGS identified SARS-CoV-2 clusters involving staff only, including some that included staff working across different care homes. SARS-CoV-2 positivity was significantly higher among staff working across different care homes than those who were working in the same care home. We found local clusters of SARS-CoV-2 infection between staff only, including those with minimal resident contact. Infection control should be extended for all contact, including those between staff, whilst on care home premises.